Effect of Melia azadirchta Fruit extract on the eggs, embryo and Juveniles of the fresh water snail Physa acuta ( Draparnaud) , at different experimental tern per a tures. - Talib Ali; Azhar Hamed (College of Education for Pure Sciences, 2007)
(Gastrula, Trochophore& hatching) as the incubation temperature increased and it was very The influence of the alcoholic extract of Melia azadirchta fruit of different concentrations at different experimental temperatures on the fecundity, embryonic development and hatching of Physa.  acuta were investigated. There was significant difference between the embryonic development reared at relatively higher temperature ( 32°C ± 2) and those reared at low temperature( 10 °C± 2 ),their was small acceleration in the rate of development at various developmental stagessignificant (3.90 days) for Trochophore stage at 30°C when it was compared with that at 10&15°C (13.6&15.6 days respectiv~ly. While · the molluscicide showed reverse effect as the temperature increase, its effect decrease to certain extend. The botanic molluscicide toxicity against eggs of P.acuta was more effective when newly laid eggs exposed to the molluscide , as well as the subsequent developmental stages affected as comparing the duration time of hatching stage & the size of juvenile snails, with those exposed to the molluscicide at Gastrula & Trochophore stages.